Perancangan Aplikasi Booking Pelaminan Online Berbasis Web Pada Jasa Rahayu Lestari Teratak Aek Nabara - Krisjayanti, Krisjayanti (Universitas Labuhanbatu, 2020)
Along with advances in technology can affect aspects of human life. At present the community is faced with problems in arranging weddings and sometimes becomes an obstacle. With the current technological advances, brides do not have to bother preparing wedding events, which all this time have only been based on notes and markers on the calendar, so there are times when the court deliberately clashes the lease schedule on the same day with the same wedding model, so finally one the customer must yield and of course be a bad judgment from the customer. The customer also needs a long time to adjust the aisle that he wants with the budget he has. Seeing this, with the development of technology now there needs to be development to build a rental information system so that the problems can be resolved and can be resolved. With the support of existing information technology, the management of data aids currently carried out can be replaced with a web-based system. Data collection methods used are observation, interview, and study of MySQL and PHP database literature. This study resulted in the Designing of Web-Based Online Application Booking Application at Jasa Rahayu Lestari Teratak Aek Nabara. Hopefully the existence of this Information system can improve the services of Assistance to the people who require booking aids.